Sierralta Ríos, Aníbal. El comercio internacional y su impacto en la cultura y el derecho - Almeida Pérez, Mariced Morayma (2020)
Currently, international trade is one of the economic activities more outstanding. It does not imply - as the author states - only transfers of goods or services; It also includes a series of elements, among which culture, technology and legal systems are included. For this reason, the international trade has direct effects, through cultural penetration or political interference, both in transnational corporations and in Recipient states and their populations. Sierralta, taking into account these new elements that are affected by economic activity, proposes a new theory: the evolutionary theory of international trade. This is raised not only as a theoretical approach, but also as the development of interdependence between the actors and the time factor in trade.